Greater Caribbean Safeguarding Initiative (GCSI) for Mutual Collaboration to Strengthen Offshore Safeguarding Efforts in the Greater Caribbean Region 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2023)
Descripción: As new pests increasingly continue to enter through various pathways, the Greater Caribbean Region (GCR) presents a significant high risk to the United States. In our effort to reduce this risk, it becomes essential to work towards mitigating that risk offshore. In July 2008, the USDA-APHIS-PPQ formalised the greater Caribbean Safeguarding Initiative (GCSI), a United States of America national programme which seeks to strengthen APHIS' partnership with countries in the GCR for the ongoing regional development of offshore pest detection and control activities for the benefit of the GCR. Objetivo General: To strengthen safeguarding efforts, in order to increase technical capacity, resources and develop long-term sustainability, within the GCR, to harmonise and regionalise mitigation capabilities that ultimately strengthens and enhances the United States mitigation and safeguarding efforts.